2016
DOI: 10.1111/jcpe.12572
|View full text |Cite
|
Sign up to set email alerts
|

Has the quality of reporting in periodontology changed in 14 years? A systematic review

Abstract: Substantial improvements have occurred. Attention is required for statistical analysis of patient losses and masking. CONSORT-NPE aspects were poorly reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In recent years, there were some studies on the reporting quality of periodontology RCTs. In 2016, Leow NM compared the reporting quality of periodontology RCTs with the RCTs 14 years ago and showed us that the reporting quality had improved but not yet optimal ( 7 ). Satish Kumar assessed the reporting quality of periodontal RCT abstracts published in 2012 and found that substantial effort is needed to improve the reporting quality ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there were some studies on the reporting quality of periodontology RCTs. In 2016, Leow NM compared the reporting quality of periodontology RCTs with the RCTs 14 years ago and showed us that the reporting quality had improved but not yet optimal ( 7 ). Satish Kumar assessed the reporting quality of periodontal RCT abstracts published in 2012 and found that substantial effort is needed to improve the reporting quality ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Past and future trends and/or expectations may be evaluated by different settings including questionnaires, consensus conferences and/or bibliometric research [16]. Bibliometric research focuses on a descriptive analysis of publications and received increasing attention in recent years [29,30]. Different aspects relevant for understanding research developments in the past, future trends, geographic origin of the authors, study design and quality, number and nature of measured outcomes, factors influencing diagnosis or the most cited articles in periodontology were the objectives of recent bibliometric studies [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that quality of RCTs in periodontology frequently did not meet recommended standards. A follow-up systematic review by the same group (Leow et al 2016) showed that dramatic improvements had occurred over 14 years in the aspects of randomization, allocation concealment and masking. In agreement with the present study, the aspect with the least adherence to required reporting standards was allocation concealment (Leow et al 2016).…”
Section: Ta B L Ementioning
confidence: 99%
“…A follow-up systematic review by the same group (Leow et al 2016) showed that dramatic improvements had occurred over 14 years in the aspects of randomization, allocation concealment and masking. In agreement with the present study, the aspect with the least adherence to required reporting standards was allocation concealment (Leow et al 2016). Publications in journals with higher IF had lower overall RoB scores and better compliance with "primary outcome" reporting, compared with papers published in lower IF journals.…”
Section: Ta B L Ementioning
confidence: 99%